Study on the process of cardiomyocyte apoptosis after pulsed field ablation - Fan, Shaobo; Jia, Fenglin; Cui, Yingjian; Wu, Dongyan; He, Le; Zhang, Fan; Xue, Zhixiao; Xu, Xinyu; Lu, Fengmin; Ma, Wei; Su, Siying; Chen, Yanpeng; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: The development of pulsed field ablation (PFA) as a new technique for pulmonary vein isolation (PVI) has been advancing rapidly in recent years. My team's previous work has shown the safety and long-term efficacy of bipolar asymmetric pulses in animal experiments. However, in ongoing clinical trials, we have observed that atrial fibrillation (AF) recurs in some patients after surgery, but the rhythm returns to normal without surgical intervention after seven days, and there is no recurrence in the follow-up.Based on this observation, we have proposed the hypothesis that myocardial cell apoptosis may play a role in AF recurrence after PFA.Our team has designed animal experiments to verify this hypothesis and further investigate the process of PFA-induced cardiomyocyte apoptosis. Methods:Pulse field ablation was performed on 15 dogs and the animals were dissected at various time points after the operation (immediately, 3 days, 7 days, 30 days, and 150 days). To obtain ablation voltage maps, electroanatomic mapping was performed before and after ablation and before dissection. The ablation area was also subjected to HE and TUNEL staining to analyze apoptosis and pathological results. Results:The edge area of the ablation in the pulmonary vein (PV) demonstrated continuous dynamic changes from 0 to 2 hours after the operation and a slight expansion of the ablation range was observed in the long-term follow-up. Myocardial intima hyperplasia was observed from 0 to 7 days. Local apoptosis was detected from 0 to 2 hours and massive, concentrated apoptosis was observed at 3 days. No recurrence of apoptosis was seen at 7 days, 30 days, and 150 days. Conclusions:The results of this study showed that after pulse field ablation (PFA), the central ablation area of the canine heart experienced immediate cardiomyocyte death. Meanwhile, cardiomyocytes in the edge ablation area underwent apoptosis, which began from 0 to 2 hours post-operation and ended between 3 to 7 days. This process occurred simultaneously with intimal thickening.In the long-term follow-up group, there was no recovery of isolation and no recurrence of cardiomyocyte apoptosis, and no change was observed in the endomyocardial intima. Keywords: atrial fibrillation,pulse field ablation, pulmonary vein isolation